Figurações da leitura: um estudo sobre o papel do narratário em "Grande Sertão: Veredas" - Lisa Carvalho Vasconcellos (2005)
Grande sertão: veredas the only novel written by Guimarães Rosa has long challenged critics concerned with its structure. In this book, an old farmer named Riobaldo narrates his adventurous youth to a foreigner, who came from the city to visit him. What makes that simple motif so interesting is the fact that none of the visitor's words are registered in the text. The reader acknowledges his existence through sings given by Riobaldo who uses several resources that indicate verbal interaction. A significant number of literary critics have compared the outsider or narratee to a prototype reader. Nevertheless, none of them hasinvestigated the matter thoroughly. That's what we intend to do. Based on the propositions of Roland Barthes about fragment and figure we created six different figures though witch the narratee appears in the book: the traveler, the neutral, the friend, the stranger, the adversary and the arbitrator. By associating those results with Barthes' conceptions of reading, the studies of Erich Auerbach, and Guimarães Rosa's personal papers, we came to the conclusion that the narratee is both a reader and a writer. We didn't try to match Riobaldo's guest to an ideal kind of reading, though. Instead, we believe that Rosa's fiction demands an open and sometimes flawed reception.